2000
DOI: 10.1007/s006040050058
|View full text |Cite
|
Sign up to set email alerts
|

Relative Cross Sections for L- and M-Shell Ionization by Electron Impact

Abstract: Results from measurements and calculations of relative L-and M-shell ionization cross sections by electron impact are presented. Measurements were performed for elements Te, Au and Bi on an electron microprobe with specimens consisting of extremely thin ®lms of the studied element deposited on thin, self-supporting, carbon layers. The relative variation of the ionization cross section was obtained by counting the number of characteristic X-rays from the considered element and shell, for varying incident electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Furthermore, our relative L 3 ionization cross sections are in excellent accord with those of Ref. [22], and also with the calculations performed with the two theoretical formalisms studied here.…”
Section: B L-subshell Ionization Cross Sectionssupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, our relative L 3 ionization cross sections are in excellent accord with those of Ref. [22], and also with the calculations performed with the two theoretical formalisms studied here.…”
Section: B L-subshell Ionization Cross Sectionssupporting
confidence: 89%
“…The (black) empty circles denote the data from Ref. Ll00 [22]. The continuous and dashed curves are, respectively, the normalized DWBA [19,50] and SCADW [17,18,20] L 3 ionization cross sections.…”
Section: A L X-ray Production Cross Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…m is a constant for each shell in the range 0.7-0.9, adjusted to fit the shape of the relationship to experiment; a similar approach has been used by Pouchou (1994), who found m to be a slowly varying function of atomic number. Direct measurements by Llovet (2000a) for the L and M shells and by Llovet (2000b) for the K shell also accord generally with this form. Finally, the multipliers q K , q L , and q M are set by experiment to match the observed intensities from each shell to one another and to those results for which the intensities are known in absolute terms.…”
Section: Intensity Of Characteristic Emission Emitted From Samplesupporting
confidence: 67%
“…This is precisely the energy range of interest for the materials characterization techniques based on x-rayemission or Auger-electron spectroscopy. As pointed out by Merlet et al [9], the scarce measurements of M-shell x-ray production cross sections found in the literature were mostly performed at very-high-incident electron energies [10,11] or were mainly focused on the energy dependence of the cross section [12][13][14]. Nevertheless, absolute experimental determinations were recently carried out in the low-overvoltage range for Au, Bi [9], Pb [15], Th [16], and U [17].…”
Section: Introductionmentioning
confidence: 99%